(untitled) (Conference Zone, 2022)
The article scientifically substantiates the study of the scientific heritage of Abu Nasr Farabi by scientists from the countries of the East and West. Everyone knows that Abu Nasr al-Farabi, known in the medieval Muslim East as the «Second Teacher» (i.e., the second after Aristotle). The study of Farabi’s heritage in modern historical, philosophical and Oriental literature is carried out in three directions.